Hidden wholesale: the drug diffusing capacity of online drug cryptomarkets - Aldridge, Judith (International journal of drug policy, 2016)
In spite of globalizing processes ‘offline’ retail drug markets remain localized and – in recent decades – typically ‘closed’, in which dealers sell primarily to known customers. We characterize drug cryptomarkets as ‘anonymous open’ marketplaces that allow the diffusion of drugs across locales. Where cryptomarket customers make stock-sourcing purchases for offline distribution, the cryptomarket may indirectly serve drug users who are not themselves cryptomarket customers, thereby increasing the drug diffusing capacity of these marketplaces. Our research aimed to identify wholesale activity on the first major cryptomarket, Silk Road 1.